2014
DOI: 10.1371/journal.pone.0098654
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Surgeons' Perception of Frail Behavior in Videos of Standardized Patients

Abstract: BackgroundFrailty is a predictor of poor outcomes following many types of operations. We measured thoracic surgeons' accuracy in assessing patient frailty using videos of standarized patients demonstrating signs of physical frailty. We compared their performance to that of geriatrics specialists.MethodsWe developed an anchored scale for rating degree of frailty. Reference categories were assigned to 31 videos of standarized patients trained to exhibit five levels of activity ranging from “vigorous” to “frail.”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Training of raters on how to use the assessment tool improves the agreement generally and is recommended for this new tool as well. The Fleiss Kappa of 42% and Kendall’s value of 50% obtained in this study are consistent with findings of other studies: that assessed agreement between thoracic surgeons rating frail behavior of patient and obtained a Fleiss Kappa of 47% and Kendall’s value of 85% [ 21 ]; and another that assessed the reliability of an injury scoring system for horses and obtained a Fleiss Kappa of 66% and Kendall’s value of 88% [ 22 ]. The Kendall’s value represents a robust measurement of agreement compared to the value generated by traditional Kappa.…”
Section: Discussionsupporting
confidence: 91%
“…Training of raters on how to use the assessment tool improves the agreement generally and is recommended for this new tool as well. The Fleiss Kappa of 42% and Kendall’s value of 50% obtained in this study are consistent with findings of other studies: that assessed agreement between thoracic surgeons rating frail behavior of patient and obtained a Fleiss Kappa of 47% and Kendall’s value of 85% [ 21 ]; and another that assessed the reliability of an injury scoring system for horses and obtained a Fleiss Kappa of 66% and Kendall’s value of 88% [ 22 ]. The Kendall’s value represents a robust measurement of agreement compared to the value generated by traditional Kappa.…”
Section: Discussionsupporting
confidence: 91%
“…A group of geriatric specialists, using an iterative process, had previously developed a set of physical characteristics based on the phenotypic criteria developed by Fried and colleagues [18] that could be portrayed in a short, silent video, including weight loss, gait speed, strength, and fatigue [19]. Three levels of physical performance (“somewhat vigorous,” “neither vigorous nor frail,” and “somewhat frail”) were assigned performance characteristics with standard metrics (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that risk estimates for surgical treatment change considerably when vignette and video pairings are discordant [19]. Risk estimates decrease somewhat after subjects view a vigorous video paired with a high-risk vignette.…”
Section: Commentmentioning
confidence: 99%
“…Videos of standardized patients were created to portray “somewhat vigorous” and “somewhat frail” behavior, hereafter referred to as “vigorous” and “frail” videos, as previously described [10,11]. The videos were silent, and depicted the standardized patient walking into an exam room, sitting in a chair, rising from the chair, walking to an exam table, and climbing onto the table.…”
Section: Methodsmentioning
confidence: 99%
“…Experienced thoracic surgeons, on visual inspection, have an ability to recognize frail characteristics similar to that of geriatricians [10]. Surgeons in practice are better than surgical residents at recognizing frailty and at incorporating factors associated with frailty in their surgical risk estimates [11].…”
Section: Introductionmentioning
confidence: 99%